2009
DOI: 10.1055/s-0029-1214711
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-administered propofol–alfentanil sedation using a patient-controlled analgesia pump compared with opioid–benzodiazepine sedation for outpatient colonoscopy

Abstract: Despite higher costs, nurse-administered propofol-alfentanil sedation using a PCA pump can provide deeper conscious sedation, comparable satisfaction, and similar complication risks compared with conventional opioid-benzodiazepine sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…In GI endoscopy, sedation has been increasingly adopted as a routine procedure by most endoscopists for improving patient tolerance and relieving patient anxiety [11]. The use of the sedative propofol has significantly increased over the past years due to its pharmacological benefits with rapid onset and short duration of action [12] resulting in rapid patient recovery upon completion of the procedure [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In GI endoscopy, sedation has been increasingly adopted as a routine procedure by most endoscopists for improving patient tolerance and relieving patient anxiety [11]. The use of the sedative propofol has significantly increased over the past years due to its pharmacological benefits with rapid onset and short duration of action [12] resulting in rapid patient recovery upon completion of the procedure [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been utilized in the prescription of propofol including the continuous infusion method, nurse‐administered propofol sedation, patient‐controlled and computer‐controlled sedation …”
Section: Discussionmentioning
confidence: 99%
“…5,15 Several methods have been utilized in the prescription of propofol including the continuous infusion method, nurse-administered propofol sedation, patient-controlled and computer-controlled sedation. [17][18][19] TCI method allows i.v. administration of propofol using an infusion pump.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that PCS can be used with nurse surveillance safely and effectively for colonoscopy. 3,22 Given the observed low incidence of adverse event rates, high sedation success rates, and minimal requirements for anesthesiologist intervention among patients who received PCS, we believe that PCS can be provided by a nurse specialist for ERCP as well. Such a nurse would need to be trained to recognize hypoventilation and other sedationrelated complications and be prepared to rescue patients from levels of sedation deeper than intended.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Propofol sedation is associated with rapid onset of action, fast recovery, good patient cooperation, and a high satisfaction level, as judged by both patients and endoscopists. Sedation is usually induced with a bolus of propofol and thereafter maintained with a constant infusion titrated individually.…”
mentioning
confidence: 99%